O-013 How Tough is the Interventional Life, the Heart Rate of a Neurointerventionalist. (26th July 2014) - Brouwer, P
Abstract : Performing neurointerventional procedures can in some cases be considered demanding. Some procedures are straightforward but we all face situations where our heart rate and blood pressure seem to rise considerably. In this presentation a graphic representation will be given of the operators' monitored heart rate during a variety of illustrative procedures. Disclosures: P. Brouwer: None.